2013
DOI: 10.1158/2159-8290.cd-13-0253
|View full text |Cite
|
Sign up to set email alerts
|

Misregulation of Pre-mRNA Alternative Splicing in Cancer

Abstract: Alternative splicing of mRNA precursors enables one gene to produce multiple protein isoforms with differing functions. Under normal conditions, this mechanism is tightly regulated in order for the human genome to generate proteomic diversity sufficient for the functional requirements of complex tissues. When deregulated, however, cancer cells take advantage of this mechanism to produce aberrant proteins with added, deleted, or altered functional domains that contribute to tumorigenesis. Here we discuss aspect… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

6
236
0
1

Year Published

2014
2014
2019
2019

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 273 publications
(243 citation statements)
references
References 99 publications
6
236
0
1
Order By: Relevance
“…The accumulation of disease-related mutations in the spliceosome, the machinery for intron recognition and removal, correlates with aberrations in alternative splicing that have been suggested to contribute to tumorigenesis (Tazi et al 2009;Zhang and Manley 2013;Sveen et al 2016). Disease-related mutations cluster in proteins involved in spliceosome assembly, particularly ones important for intron recognition, such as SF3B1 (also known as SAP155, SF3b155, and Hsh155p), SRSF1, and U2AF (Yoshida et al 2011;Quesada et al 2012).…”
mentioning
confidence: 99%
“…The accumulation of disease-related mutations in the spliceosome, the machinery for intron recognition and removal, correlates with aberrations in alternative splicing that have been suggested to contribute to tumorigenesis (Tazi et al 2009;Zhang and Manley 2013;Sveen et al 2016). Disease-related mutations cluster in proteins involved in spliceosome assembly, particularly ones important for intron recognition, such as SF3B1 (also known as SAP155, SF3b155, and Hsh155p), SRSF1, and U2AF (Yoshida et al 2011;Quesada et al 2012).…”
mentioning
confidence: 99%
“…Alterations in SF3B1 were initially discovered in myelodysplastic syndromes (MDSs) and chronic lymphocytic leukemia (CLL), together with other mutations of splicing factors, such as U2AF1, SRSF2 and ZRSR2 (refs 1-3). Importantly, these genes encode proteins that are all involved in 3 0 -splice site recognition during RNA splicing 4 . It has been shown that SF3B1 is mutated in a significant proportion (B20%) of uveal melanoma (UM), a rare malignant entity deriving from melanocytes from the uveal tract [5][6][7] , and in other solid tumours at lesser frequencies 8,9 .…”
mentioning
confidence: 99%
“…Aberrant alternative splicing events are commonly observed in cancer cells and have been implicated in many types of cancer 14,15 . For example, many genes that are involved in proliferation and invasiveness are frequently alternatively spliced, and their specific splice variants, which stimulate cell proliferation and migration, and thus contribute to the transformed phenotype, are often upregulated in tumours.…”
mentioning
confidence: 99%